Bioecologia de Microtheca semilaevis Stal, 1860 (Col.: Chrysomelidae) - Fornari, Rodrigo (2012)
The Chinese cabbage (Brassica chinensis L.) has been indicated, along with other vegetables, as an excellent alternative for Brazilian agribusiness, especially those grown in organic production system. Regarding to insect pests, that damage this crop, it shows the chrysomelid Microtheca semilaevis Stal, which cause defoliation on plants during larval and adult stages. Thus, the present work was developed to study bioecology aspects of M. semilaevis, obtaining information about biology, food preference and consumption, natural enemies and population fluctuation. In laboratory and under controlled conditions, biological aspects, such as duration, feasibility and measurement of the immature and adults; and fertility and longevity of adults were evaluated to determine fertility life table. Also in laboratory, experiments to evaluate food consumption and feeding preference of these beetles were conducted fed on leaf discs of four host varieties: Chinese cabbage, watercress (Nasturtium officinale L.), arugula (Eruca sativa L.) and mustard (Brassica juncea C.). Under field conditions, samples of natural enemies of the different development stages were taken in cultivation, besides studying the population dynamics of Microtheca spp. during Chinese cabbage crop cycle in Santa Maria, RS. The eggs have an average incubation period of 6.13 ± 0.04 days and average survival rate of 76.00%. M. semilaevis presents four larval instars, and the average duration of each instar were 2.86 ± 0.06, 1.97 ± 0.05, 1.80 ± 0.06 and 2.43 ± 0.07 days. The cycle from egg to adult is approximately 22 days. Life table fertility determined an increasing capacity of 166 times in each generation, and the average length of a generation of 49 days and finite rate of increase of 1.116 individuals / week. Larvae prefer watercress among crucifers tested, while adults prefer watercress and arugula, with lower consumption for both development stages ranging from Chinese cabbage and mustard. The peak population of larvae and adults in the field occurred in October. There was no emergence of parasitoids on larval and adult stages. However, predators were found belonging to four families with a predominance of Coccinellidae and Pentatomidae and also Vespidae and Reduviidae were found in smaller numbers. The results in this work provide subsidies that might be used for the establishment of integrated management strategies for M. semilaevis.